2019
DOI: 10.1111/1365-2745.13280
|View full text |Cite
|
Sign up to set email alerts
|

Measuring competitive impact: Joint‐species modelling of invaded plant communities

Abstract: Non‐native species can dominate plant communities by competitively displacing native species, or because environmental change creates conditions favourable to non‐native species but unfavourable to native species. We need to disentangle these mechanisms so that management can target competitively dominant species and reduce their impacts. Joint‐species distribution models (JSDMs) can potentially quantify competitive impacts by simultaneously modelling how species respond to environmental variation and to chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Many studies have documented competitively superior exotic species displacing native species (Callaway & Aschehoug, 2000;Groves et al, 2003;van Kleunen et al, 2010). In contrast, exotic species that are poor competitors, while sometimes common and widespread, are often found at lower abundance and appear to have less impact on native communities (Grice, 2006;O'Reilly-Nugent et al, 2019). Hence, differences in the relative competitive ability of invasive species may help explain differences in the extent to which they can invade and impact native ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have documented competitively superior exotic species displacing native species (Callaway & Aschehoug, 2000;Groves et al, 2003;van Kleunen et al, 2010). In contrast, exotic species that are poor competitors, while sometimes common and widespread, are often found at lower abundance and appear to have less impact on native communities (Grice, 2006;O'Reilly-Nugent et al, 2019). Hence, differences in the relative competitive ability of invasive species may help explain differences in the extent to which they can invade and impact native ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Many examples of the competitive displacement of plant species involve just one or a few competitively dominant species that disproportionately influence the composition of plant communities. For example, in a nearby temperate grassland, joint‐species modelling revealed that most plant species had little or no effect on each other, with only three of the 72 species analysed appearing to competitively displace co‐occurring species (O'Reilly‐Nugent et al 2020). Even where there is a clear competitive dominant, species can often persist in a portion of their niche space unoccupied by the competitor, with the niche space often partitioned at a fine spatial scale (Wandrag et al 2019, O'Reilly‐Nugent et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Human activities such as livestock grazing and nutrient addition have altered grasslands in ways that favour dominance by exotic grass species (McIntyre and Lavorel 1994, Seabloom et al 2015). Nevertheless, it is unclear whether exotic species dominate grasslands by competitively displacing native species at disturbed, high resource sites (O'Reilly‐Nugent et al 2020), or because those sites are better suited to exotic establishment and growth independent of competitive outcomes (Seabloom et al 2003, HilleRisLambers et al 2010). The potential for native species to facilitate the establishment of exotic species is only recently gaining attention (Lucero et al 2019, Cavieres 2021, Lortie et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although the native–exotic dichotomy offered general between‐group insights in this and many previous studies, it can sometimes be an overly broad categorization that ignores interspecific variation among natives or among exotics in environmental responses and biotic impacts (Suding et al, 2008; Supp & Ernest, 2014) — especially for the native species that are functionally more heterogeneous as a group than the exotic species. Research into the interspecific variations within native and exotic groups of species remains scarce (but see Bennett, 2014 and O'Reilly‐Nugent et al, 2020), though individual species' environmental response can now be quantified with the increasingly popular joint species distribution models (Warton et al, 2015) to understand the links between species‐level abundance and community‐level diversity under environmental change. Nonetheless, our focus on community‐level diversity remains useful by providing a broader overview of potential responses and relates to many current management practices such as the removal of an individual from a site as long as it is exotic and the use of diversity metrics for monitoring.…”
Section: Discussionmentioning
confidence: 99%